Effect of myofascial techniques for treatment of persistent arm pain after breast cancer treatment: randomized controlled trial. (April 2018) - De Groef, An; Van Kampen, Marijke; Vervloesem, Nele; Dieltjens, Evi; Christiaens, Marie-Rose; Neven, Patrick; Vos, Lore; De Vrieze, Tessa; Geraerts, Inge; Devoogdt, Nele
Objective: To investigate the effect of myofascial therapy in addition to a standard physical therapy program for treatment of persistent arm pain after finishing breast cancer treatment. Design: Double-blinded (patient and assessor) randomized controlled trial. Setting: University Hospitals Leuven, Belgium. Patients: A total of 50 patients with persistent arm pain and myofascial dysfunctions after breast cancer treatment. Intervention: Over three months, all patients received a standard physical therapy program. The intervention group received in addition 12 sessions of myofascial therapy, and the control group received 12 sessions of placebo therapy. Main measurements: Main outcome parameters were pain intensity (primary outcome) (maximum visual analogue scale (VAS) (0–100)), prevalence rate of arm pain, pressure hypersensitivity (pressure pain thresholds (kg/cm 2 ) and pain quality (McGill Pain Questionnaire). Measures were taken before and after the intervention and at long term (6 and 12 months follow-up). Results: Patients in the intervention group had a significantly greater decrease in pain intensity compared to the control group (VAS −44/100 vs. −24/100, P = 0.046) with a mean difference in change after three months between groups of 20/100 (95% confidence interval, 0.4 to 39.7). After the intervention, 44% versus 64% of patients still experienced pain in the intervention and control group, respectively ( P = 0.246). No significant differences were found for the other outcomes. Conclusion: Myofascial therapy is an effective physical therapy modality to decrease pain intensity at the arm in breast cancer survivors at three months, but no other benefits at that time were found. There were no long-term effects at 12 months either.